Star formation in the high-extinction Planck cold clump PGCC G120.69+2.66 - Anlaug A. Djupvik; João L. Yun; Fernando Comerón (The Open Journal of Astrophysics)
We investigate the star formation occurring in the Planck Galactic cold clump PGCC 120.69+2.66. Near-infrared JHKs images and K-band spectroscopy obtained with NOTCam at the Nordic Optical Telescope complemented with archive data are used to study the stellar content. In addition, millimetre line CO and CS spectra were obtained with the Onsala 20 m telescope, and sub-millimetre continuum SCUBA archive data are used to characterise the host molecular cloud. We identify a molecular cloud core traced by CO and CS emission at a distance of 1.1 kpc. In the region studied, we identify 5 submm continuum cores. Embedded in and around these dense submm cores, we find 38 young stellar objects, classified as 9 Class I, 8 Class II, and 21 near-IR excess or variability sources, accompanied by bipolar nebulosities and signs of protostellar jets. Furthermore, a very bright and reddened source is found towards this molecular cloud core. Even though its location appears to suggest its association to the star formation region, its infrared spectral type is compatible with a red supergiant, hidden behind 36 mag of visual extinction.